Analyzing Students’ Perception about the Use of TikTok Application to Enhance Students’ Speaking Skills at UIN Prof. K.H Saifuddin Zuhri Purwokerto - Alfi Hulwatun Nasichah (ELITE Association Indonesia, 2023)
In the education field, English has four skil that must be mastered. One of them is speaking skill. As we know, that there are so many students who feel anxiety to speak in English. It could be happened because inappropriate media that used in learning speaking. Nowadays, the teaching learning process in educational field has changed along with the development of the technology that used as learning media to solve the problem to help the students increase their speaking ability. One of the appropriate media platforms used is TikTok. As we know that Tik Tok has be one of the most popular applications that used to achieve the learning goals, one of them is to improve student's speaking skill. This research aim is to investigating the students’ of UIN Prof. K.H Saifuddin Zuhri Purwokerto perception toward the use of TikTok Application to improve student's speaking skill. This research is using quantitative method. The data were collected using questionnaire that distributed to 34 students at UIN Prof. K.H Saifuddin Zuhri Purwokerto. In collecting the data, the researchers used 10 question in questionnaire, which will be used to collect the data. Based on the data, the results shows that most of the students have good perception towards TikTok application and they believe that this application can help them to enhance their speaking ability. So, it can be one of the effective medium to enhance students speaking skill. Keywords: Students's Perception; TikTok Application; Speaking Skill